Perubahan Perilaku melalui Reward and Punishment di Program Sekolah - Rizqiyah , Halimatur; Warsono, Warsono; Jacky, Muhammad (The Indonesian Journal of Social Studies, 2021)
According to behaviorism theory, reward and punishment are needed to encourage desired behavior and prevent unwanted behavior. Rewards will be given to students who successfully implement the program and punishment will be given to students who violate or do not carry out the program properly. This study aims to determine the effect of giving rewards and punishments through a program called “Kata-Kata Berharga” on the behavior of ex-student of a junior high school in the Bangkalan area. The theory used in this research is the stimulus and response theory of B. F Skinner. The research is an ex-post-facto. Data analysis used simple linear regression which later showed that this program greatly influenced the behavior change of the ex-student of the junior high school, as seen from Rcount>Rtable which is 0.745>0.246. The balance between reward and punishment can create a sense of security and reward at the same time, according to the theory of motivation in Maslow's hierarchy of needs.